The Framework of Urban Landscape Reading from Walter Benjamin’s View - Mojtaba Valibeigi; Elahe Inanloo (Institut Seni Indonesia Yogyakarta, 2022)
This paper analyzes Walter Benjamin’s views to provide a useful framework and methodology for reading urban landscapes located at the interdisciplinary cross of environmental sciences, aesthetics, sociology, and cultural geography. Benjamin views the city as a place that offers a different modern experience, and the city and urban places are read both as a sign and a small world of their community. The relationship between history, the experience of presence, memory, and built environment is the basis of such a framework of reading urban landscapes, in which the present and the past time in a system together could narrate the urban experience every moment. In such a view, describing the modern experience is not essential, but rather how this experience can be fulfilled. Kerangka Penafsiran Lansekap Perkotaan Berdasarkan Pemikiran Walter Benjamin. Makalah ini menganalisis pemikiran Walter Benjamin untuk memberikan kerangka pemikiran dan metodologi yang berguna untuk menafsirkan lanskap perkotaan yang terletak di lintas disiplin ilmu lingkungan, estetika, sosiologi, dan geografi budaya. Benjamin memandang kota sebagai tempat yang menawarkan pengalaman modern yang berbeda, dan kota serta tempat-tempat di perkotaan diinterpretasikan sebagai tanda dan dunia kecil komunitas mereka. Hubungan antara sejarah, pengalaman kehadiran, ingatan, dan lingkungan yang dibangun merupakan dasar dari kerangka interpretasi lanskap perkotaan, di mana masa kini dan masa lalu berada dalam suatu sistem, yang secara bersama-sama dapat menceritakan pengalaman perkotaan di setiap saat. Dalam pandangan seperti itu, mendeskripsikan pengalaman modern bukanlah hal yang penting, melainkan bagaimana pengalaman tersebut dapat terpenuhi.